2021–2022 Florida Citrus Production Guide: Pesticide Resistance and Resistance Management - Lauren Marie Diepenbrock; Megan M. Dewdney; Ramdas Kanissery (EDIS)
This publication was updated October 19, 2021 to state that chlorpyrifos tolerances will be revoked effective 2/28/22.